Analisa gc-ms minyak atsiri Curcuma mangga Val.=GC-MS Analysis on Curcuma mangga Volatile Oil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Curcuma mangga Val. was used in traditional as anticancer. The volatile oil of C. mangga was proved to be cytotoxic. The aim of this experiments was to analyse the components of C. mangga volatile oil. The C. mangga volatile oil was found from destination of fresh rhizomes, and the components was analysed using Gas Chromato-graphy-Mass Spectrometry. The components identified were: (3-phellandrene, (J-mirsene, limonene, isopinocampheol, 2,6-nonadienal, perillene and (i-sesquiphellandrene.